Tracing the architecture of caffeic acid phenethyl ester cocrystals: studies on crystal structure, solubility, and bioavailability implications - Ketkar, Sameer; Pagire, Sudhir K.; Goud, N. Rajesh; Mahadik, Kakasaheb R.; Nangia, Ashwini; Paradkar, Anant (Crystal Growth & Design, 2016)
Caffeic acid phenethyl ester (CAPE) is a polyphenolic active compound present in popular apiproduct, "propolis", obtained from beehives, Though it has broad therapeutic capability, the bioavailability of CAPE is limited due to poor solubility. In this study, we report novel cocrystals of CAPE engineered using coformers such as caffeine (CAP), isonicotinamide (INIC), and nicotinamide (NIC) with enhanced solubility and bioavailability of CAPE. The cocrystals were prepared by microwave-assisted cocrystallization and characterized using PXRD, DSC, and Raman spectroscopy. PXRD and DSC confirm the successful formation and phase purity of CAPE-CAF, CAPE-INIC, and CAPE-NIC cocrystals. Raman spectra of CAPE cocrystals complement these results in confirming the formation of novel crystalline phases. CAPE-NIC cocrystal was further subjected X-ray crystallography to understand its molecular arrangement and hydrogen bonding in the crystal structure. The CAPE-NIC cocrystal structure is found to be stabilized by a rare 1,2-benzenediol-amide heterosynthon. Cocrystallization of CAPE with NIC improved its aqueous solubility and pharmacokinetic profile, thereby demonstrating a 2.76-fold escalation in bioavailability.

Thermomechanical effect in molecular crystals: the role of halogen-bonding interactions - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nanubolu, Jagadeesh Babu; Nangia, Ashwini (IUCRJ, 2017)
The design and synthesis of mechanically responsive materials is interesting because they are potential candidates to convert thermal energy into mechanical work. Reported in this paper are thermosalient effects in a series of halogen derivatives of salinazids. The chloro derivative, with higher electronegativity and a weaker inter-halogen bond strength (Cl center dot center dot center dot Cl) exhibits an excellent thermal response, whereas the response is weaker in the iodo derivative with stronger I center dot center dot center dot I halogen bonding. 3,5-Dichlorosalinazid (Compound-A) exists in three polymorphic forms, two room-temperature polymorphs (Forms I and II) and one high-temperature modification (Form III). The transformation of Form I to Form III upon heating at 328-333 K is a reversible thermosalient transition, whereas the transformation of Form II to Form III is irreversible and nonthermosalient. 3,5-Dibromo- (Compound-B) and 3-bromo-5-chloro(Compound-C) salinazid are both dimorphic: the Form I to Form II transition in Compound-B is irreversible, whereas Compound-C shows a reversible thermosalient effect (362-365 K). In the case of 3,5-diiodosalinazid (CompoundD) and 3,5-difluorosalinazid (Compound-E), no phase transitions or thermal effects were observed. The thermosalient behaviour of these halosalinazid molecular crystals is understood from the anisotropy in the cell parameters (an increase in the a axis and a decrease in the b and c axes upon heating) and the sudden release of accumulated strain during the phase transition. The dihalogen salinazid derivatives (chlorine to iodine) show a decrease in thermal effects with an increase in halogen-bond strength. Interestingly, Compound-B shows solid-state photochromism in its polymorphs along with the thermosalient effect, wherein Form I is cyan and Form II is light orange.